PENGEMBANGAN BASIS DATA SISTEM INFORMASI AKADEMIK PERGURUAN TINGGI BERBASIS SCHEMA MATCHING LINGUISTIC, CONSTRAINT DAN INSTANCE - Irfan, Pahrul; Hammad, Rifqi; Zuhrian, Naufal Rifqi; Azhari, Anjas Ardiyan (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2022)
Universities currently need information systems to support their activities. Bumigora University is one of the universities that implements information systems such as Siska and E-Learning. Both the system and the database of the two systems are still independent. So that the same data input is still happening on different systems. Based on these problems, it is necessary to develop a database that can connect information from Siska and E-Learning. The method used in this research is Schema Matching. The Schema Matching method used is the Linguistic, Constraint, and Instance Schema Matching method. The results showed that there were several table pairs with true positive and false positive values so that the precision, recall, and F-measure values obtained were 0.8, 1, and 0.89. The F-measure value obtained is 0.89 which is greater than 0.5 so it can be said that the scheme matching process is running quite well.